Studi Serapan Hara N, P, K dan Potensi Hasil Lima Varietas Padi Sawah (Oryza sativa L.) pada Pemupukan Anorganik dan Organik - , Sugiyanta; Fred Rumawas; M. A. Chozin; Wahju Qamara Mugnisyah; Munif Ghulamahdi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The objective of the research was to study the nutrition uptake (nitrogen, phosphorus, and potassium,) and the grain production of five rice varieties representing modern, new plant type and local varieties under application of inorganic, organic and combined inorganic-organic fertilization. Five rice varieties were Way Apoburu and IR-64 (modern varieties), Midun and Sarinah (local varieties from Sukabumi and Garut, respectively), and Fatmawati (new plant type variety). Five fertilizer treatments were (1) full recommendation dosage of inorganic fertilizer (250 kg urea/ha, 100 kg SP-36/ha, and 100 kg KCl/ha), (2) ¼ recommendation dose of inorganic fertilizer + rice straw, (3) ½ recommended dose of inorganic fertilizer + rice straw, (4) rice straw, and (5) green manure from Crotalaria juncea biomass. The results showed that there was no specific response of rice varieties to the fertilization treatments, even though there was specific nutrient uptake pattern and yield of each variety, and there was significant effect of fertilizer treatment to nutrient uptake and rice yield. Nutrient uptake and grain yield indicated that nutrient imobilisation occurred at 1stseason, however the availability of N, P, K nutrients increased at 2nd and 3rdseason on rice straw and green manure treatments. Rice straw application caused lower nutrient uptake and grain yield than full dosage inorganic fertilizer at 1st season but both were not significantly different at 2nd and 3rdseason. Application of rice straw with ½ dosage of inorganic fertilizers was not significantly different from full dosage of inorganic fertilizers in nutrient uptake and grain yield. Modern varieties showed higher level of N absorption than that of new type variety although it was not significantly different with that of local varieties, whereas the P and K uptake of modern varieties was lower than that of local and new plant type varieties. The modern varieties also showed higher level of dry grain per hill than that of local and new plant type varieties. However yield per ha of all varieties tended to be similar. Key words: uptake, efficiency, mineral nutrition, variety, lowland rice